ANALISIS PEMASARAN KACANG HIJAU DI DESA DUALASI RAIULUN KECAMATAN LASIOLAT KABUPATEN BELU. - Maria Magdalena Isa; Maria Bano; Alfetri N. P. Lango (Buletin Ilmiah Impas, 2020)
This research has been carried out in the Dualasi Raiulun Village, Lasiolat District, Belu Regency. This study aims to (1)determine the mung bean marketing channel, (2)marketing functions,(3) margins, costs, farmer's share, profit and marketing cost efficiency that affect the marketing of mung beans. Data collection uses interview techniques based on prepared questionnaires. Analysis of the data used is descriptive, economic analysis that is the calculation of Farmers' Share, Margins, profits and efficiency of marketing costs. The results of this study indicate that the (1) marketing channels in Raiulun Dualasi Village through three marketing channels namely Farmers → PPD (Village Collector Traders) → Retailers of the city of Atambua→Consumer, Second Channel Farmers → Wholesalers of the City of Atambua → Retailers of the City of Atambua→Consumer, Third Channel of Farmers → Dualasi District Retailer→Consumer.(2) Marketing functions in Railun Dualasi Village Lasiolat District include the first exchange function consisting of sales and purchase functions, second includes physical functions consisting of transportation and storage functions, and thirdly facility functions of functions financing and market information functions. (3)The lowest marketing margin is in channel one and two, which is 4,500 USD / kg, and the acquisition of the largest margin, namely in channels three, is 4,500 USD / kg and 4. The highest share of green peas in Dualasi Raiulun Village, Lasiolat District, Belu Regency is highest in channel one and two, which is 71.88%. The highest marketing profit of green beans in Raiulun Dualasi Village is in channel III which is 5.000 USD / Kg, followed by Channel I of 4,462 and channel II of 4.349 While the cost efficiency of marketing of mung beans in Raiulun Dualasi Village, Lasiolat District of Belu Regency is lowest or the smallest was channel III with I%, followed by channel Iwith 2 % and channel II with 5%.